Determination of the Correlation Dependence Between Static and Dynamic Modulus of Deformation of the Granular Sub-Ballast Layers - Ižvolt Libor; Dobeš Peter; Mečár Martin (Civil and Environmental Engineering)
Technological procedures related to the possession of tracks are often under heavy time constraints. Therefore, the attempts to apply dynamic load tests in the process of diagnostics of implemented construction works on modernised sections of railway infrastructure are increasingly frequent. When modernising constructing traffic constructions – even if dealing with technological works not related to the possession of tracks – it is often necessary to ensure a rapid progression of individual work activities or to carry out diagnostics tests in the sections with limited access to mechanisation. This test is reasonably suitable to detect critical areas not compliant with deformation standards. The combination of dynamic load tests with the static load test in these areas could, therefore, prove to save time as well as financial expenses spent on construction works inspection diagnostics. Based on the above-mentioned reasons, the presented article is focused on the analysis of set values of the dynamic modulus of deformation, obtained through light dynamic load test LDD 100, and the static modulus of deformation obtained by employing the test procedure set out in the methodology regarding the sub-ballast layers diagnostics used for German railways (DIN 18 134) and the methodology used for the Railways of the Slovak Republic (regulation ŽSR TS4).